Influence of Soaking Temperature and Concentration of Sugar Solution in the Process of Osmotic Dehydration of Curcuma (Curcuma xanthorrhiza Roxb.) - Sutarsi Sutarsi; Gadis Dien Syahda Vi; Ning Puji Lestari; Iwan Taruna; Dian Purbasari (The University of Lampung, 2024)
Curcuma (Curcuma xanthorrhiza Roxb.) is a type of medicinal plant native to Indonesia that has a moisture content of around 80-90% when harvested. Osmotic dehydration is a technique for reducing water content that can be used to overcome this problem by immersing the material in a high concentration solution. The purpose of this study was to analyze the effect of temperature and concentration of sugar solution on final water content, weight reduction, solid gain, water loss, and analyze the temperature and concentration optimal for the observed variables in curcuma dehydration process. The method used in this study was to use a completely randomized design (CRD) which was arranged in a factorial manner with 2 factors namely sugar content 50°Brix, 60°Brix, 70°Brix and immersion temperature 30°C, 40°C, 50°C with 3 repetitions. The results of the curcuma osmotic dehydration process which produces the most optimal treatment combination is at an immersion temperature of 50°C and a solution concentration of 70°Brix. This treatment combination resulted in a water content of 63.44% wb, a weight reduction of 34.73%, a solid gain of 11.81%, a water loss of 46.54%, and a total color difference of 69.64. Keywords: Curcuma, Osmotic dehydration, Sugar concentration, Temperature.